Soil treatment for grounding system purposes using sodium thiosulphate - Wan Ahmad, Wan Fatinhamamah; Ong, Khuan Shiong; Ab Kadir, Mohd Zainal Abidin; Jasni, Jasronita (2015)
There are many ways to increase the effectiveness and reliability of a grounding system meant for power system protection. One way is by lowering the ground resistance. Soil treatment with the usage of backfill materials to the grounding system is one of the most effective ways to improve the effectiveness of the grounding system. Backfill materials that applied to the grounding system can be classified into natural and chemical backfill materials. In this study, Sodium Thiosulphate and Bentonite are used as backfill materials for the purpose of soil treatment where the materials are installed in the vicinity of a grounding conductor. The purpose of conducting this study is to investigate the effectiveness of a combination and individual grounding system installations using Sodium Thiosulphate and Bentonite as backfill materials in reducing the ground resistance. Besides, this study is also conducted with a consideration of the condition of the soil for soil treatment. In the study, fall of potential method was used to obtain values of ground resistance where the results of three grounding systems are compared to the ground resistance of a reference grounding system where there is no backfill material installed in the vicinity of the conductor. The performance of the four grounding systems in ascending order is reference, Bentonite, Sodium Thiosulphate, and combination of Bentonite and Sodium Thiosulphate grounding systems. Combination of Bentonite and Sodium Thiosulphate is proposed as the best method to reduce the ground resistance because it has the lowest ground resistance and stable compared to the other grounding systems.